Plant Species in a tract of insular Atlantic Forest in Ilhabela (SP): Floristics, photographic documentation, and identification keys of arboreal dicotyledons based on vegetative characteristics - Aguirre, Andrea Garafulic [UNESP]; Teixeira, Juliana [UNESP]; Fernandes Zorzanelli, Joao Paulo; Dalla Colletta, Gabriel; Sampaio, Daniela [UNESP] (Revista Biota Neotropica, 2018)
The Ilhabela State Park (PEIb, for Parque Estadual Ilhabela in Portuguese)-located between 23 degrees 46' 28 '' south latitude and 45 degrees 21' 20 '' west latitude-is responsible for the conservation of one of the most important, and most devastated, fragments of insular Atlantic Forest. To catalog the arboreal species along the trails of the Conservation Unit, and to provide a practical instrument to facilitate the recognition of these species, we aimed with this work to conduct a floristic and photographic survey of distinct life forms and create an identification key for arboreal dicotyledonous species based on vegetative characters. We cataloged 123 species belonging to 99 genera and 46 botanical families. The best-represented families were Rubiaceae (15 spp.), Fabaceae (10), Piperaceae (10), Myrtaceae (8), Melatomataceae (7) and Lauraceae (7). We found three species threatened with extinction, two new occurrences for the state of Sao Paulo, and one plant species new to science, demonstrating the floristic importance of the region. We developed three vegetative dichotomous identification keys: to species with compound leaves; simple and opposite leaves; and alternate simple leaves. The dichotomous keys presents 97 arboreal species, distributed among 37 families, and was based on vegetative characters such as phyllotaxis, composition and shape of the limbus, presence or absence of stipules, exudate, lenticels, indument, glands and dots. We also elaborated a photographic board with 118 species as a supplementary material to support the use of the identification key.
Keywords: Insular environments; dichotomous keys; Atlantic Forest; Ilhabela State Park